Work-family conflict among Muslim women academician: The role of religion as coping strategies in Malaysian higher learning institutions - Achour, Meguellati; Ali, Boerhannueddin, Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.